EU Policy Briefing Presentations: How can studying the Arctic help us predict future European weather and climate beyond the mean? - Olsen, Steffen M.; Swingedouw, Didier; Langehaug, Helene R.; Ballester, Joan; Lopes, Nuno; Grist, Hannah; Bearzotti, Chiara (Zenodo, 2020)
Blue-Action in partnership with the EU Parliament Intergroup on Climate Change, Biodiversity and Sustainable Development and the European Climate Research Alliance, invited policy-makers, MEPs and stakeholders to join us for this briefing event on 14th October 2020. The topic under discussion was: Tipping points, extreme events and uncertainty: How can studying the Arctic help us predict future European climate beyond the mean? Researchers leading on this topic from Blue-Action presented the current state of knowledge to decision-makers and other policy-stakeholders. The event included a panel discussion with Blue-Action partners, hosting MEPS Urmas Paet and Christel Schaldemose, ECRA representative Lars H. Smedsrud, Greenland Representative Mininnguaq Kleist and European Commission representative Sigi Gruber.